METAFISIKA SERAT JATIMURTI - Siswanto, Joko (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2010)
AbstractThis article raises âSerat Jatimurtiâ as a systematic philosophy with a formal object: ontology. This article shows that: first, âSerat Jatimurtiâ maintains unity of beings autonomous. Individual beings is not it each him, but an elementary unity and binding in unity. Second, metaphysics of âSerat Jatimurtiâ have jetty at real world, but in multifarious of being there one ground of being as a being, that is Pure Reality was so-called âKahanan jatiâ (Real Being). Third, the Real Being is a fundamental idea of metaphysics of âSerat Jatimurtiâ. All their metaphysics are instructed and concentrated on the Real Being: there is nothing, only Allah, that is being which is in fact referred as âKahanan Jatiâ.Fourth, âSerat Jatimurtiâ differentiates the existence into fourstrata of being that is âgaris, lumah, jirim and kajatenâ. The four strata of being are ontological structure of entire reality that is one unity and a bundle of relationship. To comprehend it, hence, human should have dimensions of the four strata. Integration of the four dimensions in awareness, hence, human will be able to catch the overall reality. In this case there is attachment between human being and fact, subject-object.Keywords: ontology, beings, Real Being, four strata.